2022
DOI: 10.32394/rpzh.2022.0207
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of obesity and evaluation of the risk of premature death (ABSI) based on body mass index and visceral fat area

Abstract: Background. Body mass index (BMI) is the most commonly used parameter for identifying obesity. However, it is a tool that can distort the diagnosis as misdiagnose. Objective. The aim of the study was to evaluate the BMI and visceral fat area (VFA) and to determine the presence of obesity in a group of young people and to assess their suitability for use together with other parameters indicating excessive body fat and increased risk of non-communicable disease and premature death. Material and Methods. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our previous studies [24,29,51] confirmed that body composition analysis should be the basis for assessing obesity risk. In the present study, we found that women with obesity had a higher body composition parameter PBF compared to women with overweight (44.86 ± 4.31% and 38.74 ± 2.83%, respectively, p < 0.001).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Our previous studies [24,29,51] confirmed that body composition analysis should be the basis for assessing obesity risk. In the present study, we found that women with obesity had a higher body composition parameter PBF compared to women with overweight (44.86 ± 4.31% and 38.74 ± 2.83%, respectively, p < 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…Discussing obesity, it is essential to introduce the concept of Body Mass Index (BMI), with a BMI of ≥25 kg/m 2 generally considered overweight and a BMI of ≥30 kg/m 2 classified as obesity [22,23]. This index is the most commonly used criterion for identifying individuals with overweight or obesity [24], and it is applicable to both sexes and all adult age groups. However, it should be considered basic guidance, as it does not capture the proportion of fat mass and fat-free mass or the changes in these compartments among individuals [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations